2024
DOI: 10.1136/archdischild-2023-326669
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to suppress puberty in adolescents experiencing gender dysphoria or incongruence: a systematic review

Jo Taylor,
Alex Mitchell,
Ruth Hall
et al.

Abstract: BackgroundTreatment to suppress or lessen effects of puberty are outlined in clinical guidelines for adolescents experiencing gender dysphoria/incongruence. Robust evidence concerning risks and benefits is lacking and there is a need to aggregate evidence as new studies are published.AimTo identify and synthesise studies assessing the outcomes of puberty suppression in adolescents experiencing gender dysphoria/incongruence.MethodsA systematic review and narrative synthesis. Database searches (Medline, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Seven systematic reviews were commissioned by the Cass Report and published in the BMJ Archives of Disease in Childhood [2][3][4][5][6][7][8] with a single systematic review protocol registered in PROSPERO for all seven reviews 9 . To evaluate their risk of bias we applied the ROBIS tool 10 as recommended by Cochrane 11,12 .…”
Section: The Systematic Reviewsmentioning
confidence: 99%
“…Seven systematic reviews were commissioned by the Cass Report and published in the BMJ Archives of Disease in Childhood [2][3][4][5][6][7][8] with a single systematic review protocol registered in PROSPERO for all seven reviews 9 . To evaluate their risk of bias we applied the ROBIS tool 10 as recommended by Cochrane 11,12 .…”
Section: The Systematic Reviewsmentioning
confidence: 99%
“…The research carried out by York University, published in the Archives of Disease in Childhood , found that the evidence on the use of puberty blockers and hormones in young people with gender related distress was wholly inadequate, making it impossible to gauge their effectiveness or their effects on mental and physical health 4567. “No conclusions can be drawn about the impact on gender dysphoria, mental and psychosocial health, or cognitive development,” the research concluded.…”
mentioning
confidence: 99%
“…That verdict is supported by a series of review papers published in Archives of Disease in Childhood , a journal published by BMJ and the Royal College of Paediatrics and Child Health (doi:10.1136/archdischild-2023-326669 doi:10.1136/archdischild-2023-326670 doi:10.1136/archdischild-2023-326499 doi:10.1136/archdischild-2023-326500). 3456 The evidence base for interventions in gender medicine is threadbare, whichever research question you wish to consider—from social transition to hormone treatment.…”
mentioning
confidence: 99%